Case Analysis of Compensation Audit by BPJS in Hospital X Year 2023 - Yastori, Yastori; Khumaira, Nurul Fitri; Oashttamadea, Ressa (PROMOTOR, 2024)
Audit Compensation Audits cause operational activities and hospital financial systems to become disrupted and unstable. Based on a preliminary survey at the Hospital, this research aims to analyze Compensation Audit cases carried out by health insurance providers in 2023. The type of research used is Mixed Method, namely a research approach that combines or links qualitative and quantitative forms. This research was conducted in January – June 2024. The research population was 5 compensation audit cases in 2023. In-depth analysis was carried out on 5 compensation audit cases based on analysis of medical resumes, related regulations and based on ICD-10 and ICD-9-CM coding rules. Compensation Audit Case Solution, namely coders must understand medical records, claim submission documents, ICD-10, ICD-9 CM coding rules, BPJS and hospital PPK claims regulations, doctors need to provide clear, specific management and be able to know the patient's condition. treatment class from the start of admission and the health insurance verifier must have the same perception as the previous verifier and be careful in reading and analyzing claim submission documents.